Feasibility of combined surgical and endovascular carotid access for interventional treatment of ischemic stroke. (15th June 2015) - Wiesmann, Martin; Kalder, Johannes; Reich, Arno; Brockmann, Marc-Alexander; Othman, Ahmed; Greiner, Andreas; Nikoubashman, Omid
Abstract : Background: Rapid recanalization of occluded vessels is crucial for good clinical outcome in acute ischemic stroke. Endovascular treatment is usually performed via a transfemoral approach, but catheterization of the carotid arteries can be problematic in cases of difficult anatomy or vascular pathologies in some cases. Objective: To describe our experience with a technique involving surgical access to the carotid artery and consecutive transcarotid endovascular thrombectomy in patients with acute stroke. Methods: In a retrospective review of a prospectively maintained registry we identified 6 patients who underwent acute endovascular thrombectomy via a surgical access to the carotid artery. Results: Admission National Institute of Health Stroke Scale (NIHSS) ranged from 7 to 23. Intracranial recanalization (thrombolysis in cerebral infarction, TICI≥2b) was achieved in all patients (100%). Recanalization was achieved within 19±5 min after establishing carotid access. One patient developed a small neck hematoma, which was surgically removed without complications. No complications related to endovascular therapy were seen. At 3 months' follow-up, five patients had survived. Three patients (50%) had regained excellent neurological function (modified Rankin Scale, mRS 0–1). Conclusions: Surgical carotid access for endovascular stroke treatment is feasible, with considerable advantages, in patients with expected problematic access or for whom transfemoral endovascular carotid access has failed.